Research On the Characteristics of Sediment and the Release Law of Nitrogen and Phosphorus Pollutants in Landscape Lake. Issue 1 (1st February 2022) - Zhu, Zhaoliang; Zhou, Hao; Li, Qi; Zou, Jiale; Liu, Mengmeng
Abstract: Under the premise that the external input of nitrogen and phosphorus is controlled, the endogenous release has become the dominant factor of lake eutrophication. In order to understand the degree of eutrophication of the landscape lake and the release of nitrogen and phosphorus in the sediment, a sediment lake in Jinan was used as a test object, three sampling points were set near the inlet, outlet and reed bushes of the landscape lake to collect water samples. And sediment samples, the three indicators of TN, NH4+-N and TP in the water body and TN, NH4+-N, TP, pH, DW, LOI in the sediment were analyzed. Release of TN, NH4+-N and TP in sediments under different temperature, pH, dissolved oxygen (DO), and disturbance conditions. The results show that both elevated temperature and low DO can accelerate the release of nitrogen and phosphorus in the sediment, while high DO can inhibit the release of N and P in the sediment; acidic conditions are favorable for the release of TN and NH4+-N, and alkaline conditions are favorable for TP release; disturbance can accelerate the release of nitrogen in the sediment, but has little effect on total phosphorus release.